Islam and Malay in Borneo - Dian Kartika Sari (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
Islam and Malay are undeniably inseparable from Borneo Island. This book elaborates the writer’s thoughts about Islam and Malay, especially in Borneo Island. Hermansyah himself was triggered by the small number of literatures or research on Borneo Island. Therefore, those reasons encouraged him to write more about Borneo and its living society. Islam and Malay in Borneo consists of eight chapters that present various kinds of Malay and Islam comprehensively. Chapter one is about the identity of Islam and Malay. To begin with, Malay, once, was considerably identical to Islam. If someone embraces Islam, then he or she will be considered a Malay, no matter his/her ethnic background. Nevertheless, in line with the social and political life, the idea has also been shifted.